Targeted Internal Trapping to Dilated Portion for Ruptured Vertebral Artery Dissection - Yoshida, Masahiro; Tashiro, Ryosuke (Journal of Neuroendovascular Therapy, 2019)
Objective: After internal trapping for ruptured vertebral artery dissection (VAD), serious complications related to medullary infarction influence the prognosis.Methods: The subjects were 15 patients with ruptured VAD who had undergone internal trapping between 2004 and 2017. Targeted embolization of dilated segment was performed while neither adjacent stenotic sites nor normal segments were embolized. We retrospectively analyzed the incidence and extent of medullary infarctions, neurologic sequelae, and outcome.Results: In all patients, endovascular procedures were successful. There were no intraoperative complications. In two patients, embolization with the double-catheter method through bilateral approaches was performed. Postoperative medullary infarction was noted in two patients, but they had dorsolateral-type minor infracted foci. There were no serious sequelae in any patient, and there were no rebleedings during the follow-up period.Conclusion: The results suggest that internal trapping in which the extent of embolization is limited to the site of morbid dilation prevents rebleeding, reducing the risk of postoperative medullary infarctions. Tight packing of a dilated segment with the preservation of perforators from vertebral arteries (VAs) is extremely important. The double-catheter method through bilateral approaches may be useful for tight packing of the dilated segment of ruptured VAD.